Despite initial "kicking and screaming" unstably housed persons report high satisfaction with representative payee program. Issue 2 (15th June 2015) - Davis, Dana; Hawk, Mary; McLaughlin, Jamie; Brincko, Terri; King, Miranda; Farmartino, Christina
Abstract : Purpose: – The purpose of this paper is to explore unstably housed persons satisfaction with representative payee services. Design/methodology/approach: – Surveys were distributed through two different methods, which consisted of mailings and dispersal by program staff members. Findings: – Participants overwhelmingly reported that they were satisfied with representative payee services with 77 percent of the stand-alone housing participants and 86 percent of the scattered site participants reported being "satisfied" or "very satisfied" with representative payee services. Similarly, 92 percent of stand-alone participants and 82 percent of scattered site participants reported being satisfied with their abilities to care for their needs. The lowest reported satisfaction with the program was with the timeliness of getting spending checks, with 85 percent of participants being satisfied in the stand-alone location and only 63 percent of participants reporting satisfaction in the scattered site setting. Research limitations/implications: – This research is limited by the fact that it is an evaluation of one program and does not have a comparison group. Additionally, clients self-selected to participate in the research and results are not generalizable. Future research should ascertain whether aspects of harm reduction and peer staff have an impact on client outcomes as well as representative payee satisfaction. The study was conducted in a metropolitan area in the Northeast USA, which includes the city of Pittsburgh, Pennsylvania and surrounding areas. Given that this region includes both city and suburban areas, it is likely the results are translatable to multiple geographic areas. Practical implications: – Results of this research indicate that use of harm reduction and peer staff could be factors in client satisfaction with representative payee services thereby increasing the possibility that clients will sign up for this service and receive the benefits of the program. Social implications: – Having a representative payee program imposed on clients whether voluntarily or involuntarily can be an extremely anxiety provoking experience. Increasing satisfaction with this service will lend to improved quality of life for clients as well as improved relationships with providers which may lead to more engagement in care. Originality/value: – This paper provides a new perspective on representative payee programs since it shows positive satisfaction, as well as use of harm reduction and peer staff, which varies from previous studies.